Fatores determinantes do disclosure voluntário sob o enfoque da sustentabilidade: uma análise das empresas dos países do BRIC - Gomes, Paulo Henrique Vieira (2012)
The disclosure of volunteer information is characterized as a matter of business ethics and corporate responsibility. The publication of sustainability reports aimes, in addition to communicating the widest range of stakeholders responsible practices throughout the supply and operating chain of the company, to consolidate its management in a sustainable position. In this perspective, this study aims to verify whether there is a significant relationship between the economic and financial characteristics and voluntary disclosure of information with a focus on sustainability in publicly traded companies from emerging economies: Brazil, Russia, India and China (BRIC). The economic and financial characteristics are treated as economic incentives that motivate companies to adhere to practices of voluntary disclosure. The economic incentives analyzed were: profitability, capital market performance, size, indebtedness, effect of activity on the environment and country. The voluntary disclosure level was measured from five perspectives: the level of adherence to the GRI reporting, economic disclosure, environmental disclosure, social disclosure and sustainable disclosure. The research has a quantitative approach because it is an explanatory study to evaluate the effect of causal hypotheses. It was analyzed information from 93 publicly traded companies of BRIC members countries that publish their sustainability reports on the GRI G3 model. The data were analyzed using the descriptive statistics and multiple linear regression tools. From the obtained results, it can infer that the level of voluntary disclosure of information focused on the issue of sustainability can be associated with the pre-existence of economic incentives. The performance in the capital market and the size affected positively the level of disclosure. Thus, it can be inferred that larger firms with high performance in the capital market are potentially more transparent about the disclosure of sustainability. The factor Country affected negatively the level of disclosure, indicating that companies hosted in countries with higher HDI have a lower contribution to the voluntary disclosure under the focus of sustainability according to the guidelines of the GRI report. The economic and financial characteristics profitability, indebtedness, and the effect of activity on the environment had no influence on the studied disclosure.